Impact of incident myocardial infarction on the risk of venous thromboembolism: the Tromsø Study - Balteskard Rinde, Ludvig; Lind, Caroline; Småbrekke, Birgit; Njølstad, Inger; Mathiesen, Ellisiv B.; Wilsgaard, Tom; Løchen, Maja-Lisa; Mathiesen Hald, Erin; Vik, Anders; Brækkan, Sigrid Kufaas; Hansen, John-Bjarne; Rinde, Ludvig Balteskard (Journal of Thrombosis and Haemostasis, 2016)
Manuscript. Published version available at http://dx.doi.org/10.1111/jth.13329 Background: Recent studies have demonstrated an association between venous thromboembolism (VTE) and arterial thrombotic diseases. Objectives: We aimed to study the association between incident myocardial infarction (MI) and VTE in a prospective population-based cohort. Methods: Study participants (n=29 506) were recruited from three surveys of the Tromsø Study (conducted in 1994-95, 2001-02 and 2007-08) and followed through 2010. All incident events of MI and VTE during follow-up were recorded. Cox-regression models with age as time scale and MI as a time-dependent variable were used to calculate hazard ratios (HR) of VTE adjusted for sex, BMI, blood pressure, diabetes mellitus, HDL-cholesterol, smoking, physical activity and education level. Results: During a median follow-up of 15.7 years, 1 853 participants experienced a MI and 699 experienced a VTE. MI was associated with a 51% increased risk of VTE (HR 1.51; 95% CI 1.08-2.10) and a 72% increased risk of pulmonary embolism (PE) (HR 1.72; 95% CI 1.07-2.75), but not significantly associated with risk of deep vein thrombosis (DVT) (HR 1.36, 95% CI, 0.86-2.15). The highest risk estimates for PE were observed during the first sixth months after the MI (HR 8.49; 95% CI 4.00-18.77). MI explained 6.2% of the PEs in the population (population attributable risk) and 78.5% of the PE risk in MI-patients (attributable risk). Conclusions: Our findings indicate that MI is associated with a transient increased risk of VTE independent of traditional atherosclerotic risk factors. The risk estimates were particularly high for PE.